Self‐Compassion, Affect, and Body Image in College Women. Issue 2 (6th July 2019) - Schmidt, Christa K.; Raque‐Bogdan, Trisha L.; Hollern, Emily A.
Abstract : The aim of this study was to understand the relationships between self‐compassion, positive affect, negative affect, and variables representative of positive body image for college women. Regression analyses indicated that self‐compassion and affect accounted for 39% and 30% of the variance, respectively, in body appreciation and body image quality of life. Mediational analyses demonstrated that positive affect mediated the relationships between self‐compassion and both indicators of body image. Implications for college counseling are discussed.